Principals’ Empowering Leadership Practices and Teachers’ Job Performance in Public Senior Secondary Schools, Education District II, Lagos, Nigeria - Orunbon1, Nurudeen Olalekan; Beyioku 2, Joseph Bankole; Makinde3, Olawumi Bukola (Universitas PGRI Madiun, 2024)
This study examine the relationship between principals' empowering leadership practices and teachers' job performance in public senior secondary schools, Education District II, Lagos, Nigeria. Two hypotheses (tested at 0.05 level of significance) were set to serve as guides for the study. Correlational and descriptive research designs were adopted, its population comprised 53 Principals, and 3,342 teachers in public senior secondary schools in Lagos State Education District V. The sample size for the study through the use of Yaro Yameni was 358. Two main instruments were used to collect data after ensuring their validity and establishing their reliability using test-retest method. These included ‘Principals’ Empowering Leadership Practices Questionnaire (PELPQ) and Teachers’ Job performance Questionnaire (TJSQ). Analysis was carried out using Pearsons Product-Moment Correlation Analysis using the Statistical Package for Social Science (SPSS) version 24.0. Findings indicate that there was a negative and weak correlation between innovative behaviour and teachers’ job performance (r = -.385, P<.000); and study further found that a strong correlation between job autonomy and teachers’ job performance (r = .960, P<.000). The study concludes that principals empowering leadership practices viz: practice of professional development, innovative behaviour and job autonomy enhance teachers’ job performance. The study therefore recommended that school principals must attend leadership development programmes, specifically leadership coaching, which also prepare managers for school organisation challenges.